2020
DOI: 10.1155/2020/1492980
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Strengthening of RC Beams with Near‐Surface Mounted Steel Bars

Abstract: e strength of reinforced concrete members can be enhanced by using the externally bonded reinforcement (EBR) and nearsurface mounted (NSM) methods. However, very few studies have adopted the NSM method for torsional strengthening. Although previous studies have reported the efficacy of using epoxy-resin-bonded NSM steel bars in increasing the flexural and shear strength of RC beams, no study has examined the use of steel bars and epoxy adhesives for torsional strengthening.erefore, this study investigates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…A comparison of the experimental peak strength of test miniatures using spiral stirrups and closed stirrups with diverse spacing between stirrups. Geometrical similitude has been preserved stress similitude for the steel as shown in Equation 1 [23]. Table 3 show test results for prototype with diverse stirrups spacing.…”
Section: Dissipated Energymentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the experimental peak strength of test miniatures using spiral stirrups and closed stirrups with diverse spacing between stirrups. Geometrical similitude has been preserved stress similitude for the steel as shown in Equation 1 [23]. Table 3 show test results for prototype with diverse stirrups spacing.…”
Section: Dissipated Energymentioning
confidence: 99%
“…As a result, constructing and testing economically viable reinforcing methods for boosting the torsional capacity of RC beams is an essential part. The staggered spiral tie is one of these techniques that has shown exciting results in increasing the torsional capacity [21][22][23][24]. The experimental torsional capacity values were compared to torsion strength values given by the ACI 318-14 [26] code and Eurocode-2 [27].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the performance of the structure is enhanced, so automatically the constructability is developed and the cost is lower [12]. In addition, Chalioris & Karayannis [13], and Askandar & Mahmood [14] found that using the spiral configuration as transverse reinforcement significantly improved the performance of torsional beams. Thus, the spiral stirrups used as transverse reinforcement in RC beams are considered a promising technique to improve both the torsional behaviour and the torsional capacity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers have adopted carbon fiber reinforced polymer (CFRP) as strengthening materials due to its high strength to weight ratio. But there are very limited researches dealt with using steel bars as strengthening materials such as strengthening of corbels (Shakir and Kamonna 2018) shear strengthening of beams (Thamrin et al 2019), torsional strengthening of beams (Askandar and Mahmood 2020) flexural strengthen of continuous beam (Abdzaid and Kamonna 2019) and deep beams Al-Issawi 2018, Al-Issawi andKamonna 2020). There is very limited knowledge of adopting the NSM method by steel bars for strengthening of continuous one-way RC slabs, although it is availability in addition to it is ability of accounting of redistribution load beyond formation of plastic hinge which may occur in continuous members.…”
Section: Introductionmentioning
confidence: 99%